The Evolution of NATO’s Cybersecurity Policy - AFŞAR, Önder Aytaç (Cyberpolitik Journal, 2022)
The North Atlantic Treaty Organization (NATO) strives to adapt to new security risks, politically, strategically, and technologically to changing conditions. During the Cold War, the Soviet Union was a major threat. Recently, NATO has started to expand into new regions outside of the area with new security problems and has started to focus on cyberspace which differs from traditional military defense understanding. In this framework, since 2016, it has been successfully managing cyberspace threats by accepting cybersecurity as a battlefield. NATO is moving towards a broader understanding of cyberspace as a very high-tech field. This study focuses on the developments in the alliance in line with NATO’s cybersecurity policies. In this context, it examines the alliance’s institutions and initiatives and points to the cyber challenges facing NATO in cyberspace. In this study, the development of NATO’s cybersecurity policy, its understanding in cyber defense, and the recent transformation of NATO’s cybersecurity strategy are evaluated.